Boosting Entrepreneurial Motivation Through Community Service Programs for Disaster-Affected Communities In Pasigala - Fatma, Fatma; Dede Arseyani Pratamasyari; Noor Riefma Hidayah; Moh. Taufik Ridha (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2023)
Disasters only bring impacts, particularly on the economic aspects of communities. All aspects, both directly and indirectly, ultimately lead to the loss of income potential for the community as a livelihood. Therefore, one of the efforts to address these issues, especially for household economies, is to cultivate entrepreneurial spirit through community engagement activities in the form of Islamic entrepreneurship education. This activity aims to increase entrepreneurial interest among disaster-affected communities. The activity was carried out at Huntap Duyu with 50 participants in an offline session at the Huntap Duyu Mosque. The method used was through presentations and discussions with the participants. The activity's outcome is the community's increased interest in entrepreneurship to enhance household economic self-reliance.